2004
DOI: 10.1051/0004-6361:20040183
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Canis Major stellar over-density as due to the Galactic warp

Abstract: Abstract. Proper-motion, star counts and photometric catalog simulations are used to explain the detected stellar over-density in the region of Canis Major, claimed to be the core of a disrupted dwarf galaxy (CMa, Martin et al. 2004, MNRAS, 348, 12; Bellazzini et al. 2004, [arXiv:astro-ph/0311119]), as due to the Galactic warp and flare in the external disk. We compare the kinematics of CMa M-giant selected sample with surrounding Galactic disk stars in the UCAC2 catalog and find no peculiar proper motion sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
129
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 26 publications
(40 reference statements)
7
129
0
1
Order By: Relevance
“…An alternative scenario presents the Monoceros Ring as the result of a distortion of the Galactic plane (Momany et al 2004(Momany et al , 2006Hammersley & López-Corredoira 2011). These studies suggest that the observed star counts are reproducible considering a flared thick disk without a cut-off at ∼ R 14 kpc.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…An alternative scenario presents the Monoceros Ring as the result of a distortion of the Galactic plane (Momany et al 2004(Momany et al , 2006Hammersley & López-Corredoira 2011). These studies suggest that the observed star counts are reproducible considering a flared thick disk without a cut-off at ∼ R 14 kpc.…”
Section: Introductionmentioning
confidence: 61%
“…One of the leading interpretations is that the Monoceros Ring is the remnant of a past accretion event (e.g., Conn et al 2005;Jurić et al 2008;Chou et al 2010;Sollima et al 2011), similar to that generated by the disruption of the Sagittarius (Sgr) dwarf galaxy, which is orbiting around our Galaxy in an almost polar orbit (e.g., Ibata et al 1994;Majewski et al 2003;Bonifacio et al 2004;Martínez-Delgado et al 2004;Martin et al 2004;Bellazzini et al 2006;Belokurov et al 2006;Siegel et al 2007;Koposov et al 2012). In contrast to Sgr, Monoceros lacks a known progenitor system, though it has been proposed and later discarded that the Canis Major overdensity is the accreted system that formed Monoceros (Martin et al 2004;Momany et al 2004Momany et al , 2006Martínez-Delgado et al 2005;Bellazzini et al 2006;Moitinho et al 2006;Butler et al 2007;Mateu et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…There is also strong evidence for another large stream, the Monoceros stream ( Newberg et al 2002;Yanny et al 2003), which forms a ringlike structure around the Milky Way (Ibata et al 2003). Several authors have argued that the parent galaxy of the Monoceros stream lies in the constellation Canis Major, but there is considerable controversy over this association and even the existence of the Canis Major galaxy (e.g., Martin et al 2004;Momany et al 2004;Martínez-Delgado et al 2005;Carraro et al 2005;Peñarrubia et al 2005). These ongoing merger events may be only the most recent examples of a long history of mergers that built the Milky Way from an ensemble of smaller systems, as proposed by the hierarchical picture of galaxy formation (e.g., Bullock & Johnston 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative proposal is that the Ring is a manifestation of the Galactic warp [10,11]. In this paper we explore a different proposal altogether, namely, that the Monoceros Ring of stars formed as a result of the gravitational forces exerted by the second caustic ring of dark matter in the Milky Way [12].…”
Section: Introductionmentioning
confidence: 99%